On a Local Fractional Wave Equation under Fixed Entropy Arising in Fractal Hydrodynamics - Yu Zhang; Dumitru Baleanu; Xiaojun Yang (Entropy, 2014)
In this paper, based on fixed entropy, the adiabatic equation of state in fractal flow is discussed. The local fractional wave equation for the velocity potential is also obtained by using the non-differential perturbations for the pressure and density of fractal hydrodynamics.